2009
DOI: 10.1083/jcb.200807047
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase C–mediated hydrolysis of PIP2 releases ERM proteins from lymphocyte membrane

Abstract: Mechanisms controlling the disassembly of ezrin/radixin/moesin (ERM) proteins, which link the cytoskeleton to the plasma membrane, are incompletely understood. In lymphocytes, chemokine (e.g., SDF-1) stimulation inactivates ERM proteins, causing their release from the plasma membrane and dephosphorylation. SDF-1–mediated inactivation of ERM proteins is blocked by phospholipase C (PLC) inhibitors. Conversely, reduction of phosphatidylinositol 4,5-bisphosphate (PIP2) levels by activation of PLC, expression of ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
120
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(126 citation statements)
references
References 50 publications
4
120
2
Order By: Relevance
“…␤⌱ versus ␤⌱⌱ spectrin (also known as fodrin) versus ␤⌱⌱⌱ spectrin) (12,13), as well as direct linkages of spectrin to the membrane that do not involve ankyrin, such as the interaction of the ␤-spectrin PH domain with phosphatidylinositol 4,5-bisphosphate (PIP2) (35) and PKC␤ (36,37) or the interaction of its associated ␣⌱⌱ spectrin subunit with G-protein-coupled receptors (38). Actinmembrane linkages mediated by the ERM family of proteins (39) or variable partitioning of the spectrin membrane complex into lipid raft domains (13) could also contribute to the observed heterogeneity. Interestingly, all of the latter interactions (PIP2 binding, ERM-mediated attachment, and lipid raft partitioning) are modulated during lymphocyte activation (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…␤⌱ versus ␤⌱⌱ spectrin (also known as fodrin) versus ␤⌱⌱⌱ spectrin) (12,13), as well as direct linkages of spectrin to the membrane that do not involve ankyrin, such as the interaction of the ␤-spectrin PH domain with phosphatidylinositol 4,5-bisphosphate (PIP2) (35) and PKC␤ (36,37) or the interaction of its associated ␣⌱⌱ spectrin subunit with G-protein-coupled receptors (38). Actinmembrane linkages mediated by the ERM family of proteins (39) or variable partitioning of the spectrin membrane complex into lipid raft domains (13) could also contribute to the observed heterogeneity. Interestingly, all of the latter interactions (PIP2 binding, ERM-mediated attachment, and lipid raft partitioning) are modulated during lymphocyte activation (39).…”
Section: Discussionmentioning
confidence: 99%
“…Actinmembrane linkages mediated by the ERM family of proteins (39) or variable partitioning of the spectrin membrane complex into lipid raft domains (13) could also contribute to the observed heterogeneity. Interestingly, all of the latter interactions (PIP2 binding, ERM-mediated attachment, and lipid raft partitioning) are modulated during lymphocyte activation (39). Disruption of the actin-spectrin-ankyrin complex by the N-5 FIGURE 6.…”
Section: Discussionmentioning
confidence: 99%
“…The spherical shape of leukocytes is also maintained by phosphorylated ERM proteins and an actin cortex. 26 Furthermore, phosphorylated ERM proteins and actin filaments are localized at microvilli. 18,19 Antisense oligonucleotides against ERM expression perturb microvilli, 27 indicating that ERM proteins are essential for microvillus formation and/or maintenance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that the SDF-1-CXCR4 interaction is the major regulatory element for the trafficking, retention, and adhesion of HSCs and HPCs. 30,31 Taken together with the effect of SDF-1 on microvillus collapse of lymphocytes, 26,29 alterations of HPC/HSC morphology can be caused by the SDF-1-CXCR4 interaction. Thus, cell adhesion of HPCs and HSCs may be regulated by cell shape, and CD34 might play significant roles in the formation and/or maintenance of cell shape and adhesion.…”
Section: Acknowledgmentsmentioning
confidence: 99%
“…Integrin-mediated modulation of zinc-permeable ion channels, such as NMDA receptor channels (Juhász et al, 2008;Lin et al, 2003), AMPA receptor channels (Cingolani et al, 2008;Juhász et al, 2008) and Ltype Ca 2+ channels (Waitkus-Edwards, 2002;Wu et al, 2001), has been previously documented, but little is known about the details of these regulatory mechanisms beyond their FAK-activity dependence or modulation by Src. Notably, one study reported a role for FAK in promoting the activity of phospholipase C (PLC)-γ1 (Zhang et al, 1999), which is responsible for mediating the hydrolysis of membrane-bound PIP 2 into inositol 1,4,5-trisphosphate (IP 3 ) and diacylglycerol (Hao et al, 2009;van Rheenen et al, 2005). Importantly, PIP 2 has been shown to be a critical cofactor for the function of various ion channels (Brown et al, 2007;Gamper and Shapiro, 2007;Suh and Hille, 2008), including zinc-permeable TRPM7 (Runnels et al, 2002), voltage-gated calcium channels (Lechner et al, 2005), and NMDA channels (Mandal and Yan, 2009), such that depletion of PIP 2 through PLC-mediated hydrolysis results in channel inhibition.…”
Section: Plc-mediated Pip 2 Hydrolysis Underlies Inhibition Of Zinc Ementioning
confidence: 99%